KONTRIBUSI KERAJINAN TIRAI TERHADAP PENDAPATAN DAN KONSUMSI KELUARGA PETANI DI DESA RANTAU DURIAN I KECAMATAN LEMPUING JAYA OGAN KOMERING ILIR - AISAH (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2018)
Rantau Durian I Village also has the potential for plant development in both the food crop sector and plantation crops, most of the Rantau Durian I Village area is production land or rice fields. When viewed from the irrigation point of view, rice fields are rainfed which only produce once a year, this is the reason why some of the rice fields in the village have changed their function as rubber plantations which are considered by the community to be more profitable. However, the main problem of rubber plants at this time is low rubber production and the raw materials produced are of low quality, so the price received by farmers is relatively low. This condition makes the people in the village have household activities that can support their economy after returning from tapping rubber for approximately three to four hours, so that the remaining time can be used for making curtains.The research objectives are: 1). This is to determine the price margin for curtain marketing at the village level of Rantau Durian I, Lempuing Jaya District, OKI. 2). This is to find out how much the curtain income will be on the income and consumption of farm families from the point of view of marketing time during the months of the big day (Eid, New Year). The results show that the marketing margins on retail and wholesales are different. Where retail sales or farmers sell directly to consumers is IDR 18,000. Whereas farmers sell to large parties with a large volume of Rp. 15,000, so the marketing margin is Rp. 3,000. The contribution of curtain crafts to the income of farmer families in Rantau Durian I Village was 24%. Meanwhile, the contribution of curtain to the consumption of farmer families in Rantau Durian I Village is 40%.